2008
DOI: 10.1111/j.1467-6494.2008.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

The Heritability of Personality Is Not Always 50%: Gene‐Environment Interactions and Correlations Between Personality and Parenting

Abstract: Twin studies of personality are consistent in attributing approximately half of the variance in personality to genetic effects, with the remaining variance attributed to environments that make people within the same families different. Such conclusions, however, are based on quantitative models of human individual differences that estimate genetic and environmental contributions as constants for entire populations. Recent advances in statistical modeling allow for the possibility of estimating genetic and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(133 citation statements)
references
References 51 publications
5
123
0
2
Order By: Relevance
“…In spite of the controversial causal relation between emotion regulation and emotionality, there is a modest to strong negative correlation (r = -.20 to -.60) between these two concepts in children of different ages (Eisenberg et al 1993;Eisenberg et al 1997). Moderate to high heritability of emotionality has been consistently reported (ranging .34 to .71) in twin studies of temperament in childhood and adolescence (Ganiban et al 2008;Gjone and Stevenson 1997;Krueger et al 2008;Schmitz et al 1996). As is typically found in behavioral genetic studies of temperament, the remaining variance is largely due to nonshared environmental effects.…”
Section: Future Directions: Developmental Behavioral Geneticsmentioning
confidence: 90%
“…In spite of the controversial causal relation between emotion regulation and emotionality, there is a modest to strong negative correlation (r = -.20 to -.60) between these two concepts in children of different ages (Eisenberg et al 1993;Eisenberg et al 1997). Moderate to high heritability of emotionality has been consistently reported (ranging .34 to .71) in twin studies of temperament in childhood and adolescence (Ganiban et al 2008;Gjone and Stevenson 1997;Krueger et al 2008;Schmitz et al 1996). As is typically found in behavioral genetic studies of temperament, the remaining variance is largely due to nonshared environmental effects.…”
Section: Future Directions: Developmental Behavioral Geneticsmentioning
confidence: 90%
“…The effect of gene-environment correlation (rGE) and interaction (G 9 E) could also explain parts of the phenotypic variance. For example, Krueger et al (2008) found that the relationship between parents and their children moderated genetic influences on the broad personality domains of negative and positive emotionality. Relatively low or high levels of Regard and Conflict were associated with different contributions of heritability.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…The most convincing evidence for hereditary contributions to personality has come from twin, family and adoption studies. These studies have demonstrated that monozygotic (identical) twins are more similar in personality than are dizygotic (fraternal) twins (Riemann, Angleitner, & Strelau, 1997), that adopted children are more similar in personality to their biological parents than to their adoptive parents (Loehlin, Willerman, & Horn, 1985), and that monozygotic twins reared apart are more similar in personality than are dizygotic twins reared together (Hershberger, Plomin, & Pedersen, 1995;Pedersen, Plomin, McClearn, & Friberg, 1988 Krueger, South, Johnson, & Iacono, 2008).…”
Section: Personality Continuity and Sport Participationmentioning
confidence: 99%